ANALYSIS OF PLANNING CONSTRUCTION MAIN ROAD DEVELOPMENT PLTU TANJUNG JATI A - Tubagus CiptaPerdana Harta; Martinus Agus Sugianto (Journal of Green Science and Technology, 2018)
Construction of Main Road at TanjungJati steam power plant which is currently being implemented does not yet have pavement structure, moving the writer to make the research object by analyzing the rigid pavement thickness planning by paying attention to vehicle load repetition factor because the average daily traffic (LHR) the road is not much. In addition to the analysis of pavement thickness planning in this study will also analyze the construction management for road construction in PLTU TanjungJati be efficient, effective and have good quality.The method used in this research is qualitative method by emphasizing secondary data, Vehicle Load Repetition Analysis, Rigid Pavement Thickness Analysis, Volume Calculation Analysis, Cost Analysis, Bar Chart Method, S Curve and Critical Path Method.Keywords: Highway, Rigid Pavement, Concrete Pavement, Project Management, Bar Chart Method, S Curve and CPM.